Navigating the Web: A Study on Network Topology and Information Flow - Shailesh Parmar; Anand Daram (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The internet, as a complex network of interconnected nodes, presents a dynamic landscape for the dissemination and flow of information. This study delves into the intricate interplay between network topology and information propagation, aiming to elucidate the mechanisms underlying navigation through the web. By analyzing various network models and employing techniques from graph theory, we investigate how the structural characteristics of the web influence the spread of information. Furthermore, we explore the role of key factors such as node centrality, clustering, and connectivity patterns in shaping information diffusion dynamics. Through empirical analysis and computational simulations, our findings shed light on the mechanisms governing the flow of information across the web, offering insights into strategies for effective navigation and content dissemination in the digital age.